Architectonics of Podkoní a žák - Všetička, František (Bohemica Olomucensia, 2018)
Podkoní a žák, a versed composition from the late 14th century includes three protagonists. At the beginning and at the end of the poem, there is a narrator, who is involved in the story (personal narrator). A stableman and a trainee, other protagonists, have an argument about the assets of their own status. The extent of their monologues is basically the same, each of which has a triadic ordering. The composition has a storyline meter. The predominant quality of this work, which is of a parody character, is the rhyme.
Keywords: personal narrator; protagonists; monologues; storyline meter; rhyme; parody